Eyetracking during picture naming predicts future vocabulary dropout in progressive anomia. Issue 4 (21st April 2022) - Reilly, Jamie; Flurie, Maurice; Ungrady, Molly B.
ABSTRACT: The dynamic and unpredictable nature of expressive vocabulary dropout in progressive anomia presents a challenge for language intervention. We evaluated whether eye gaze patterns during naming could predict anomia for the same items in the near future. We tracked naming accuracy and gaze patterns as patients with semantic ( n = 7) or logopenic ( n = 2) variants of Primary Progressive Aphasia or amnestic Alzheimer's Disease ( n = 1), named photographs of people and objects. Patients were tested three or more times spaced roughly evenly over an average duration of 19.1 months. Target words named accurately at baseline were retrospectively coded as either known (i.e., consistently named) or vulnerable (i.e., inaccurately or inconsistently named) based on naming accuracy over the study interval. We extracted gaze data corresponding to successful naming attempts and implemented logistic mixed effects models to determine whether common gaze measures could predict each word's naming status as known or vulnerable. More visual fixations and greater visual fixation dispersion predicted later anomia. These findings suggest that eye tracking may yield a biomarker of the robustness of particular target words to future expressive vocabulary dropout. We discuss the potential utility of this finding for optimizing treatment for progressive anomia.